A new species of Tulostoma genus from Siberia - Vlasenko, Vyacheslav A.; Vlasenko, Anastasia V. (Phytotaxa, 2023)
We described a new Tulostoma species based on morphological and molecular data. Its characteristic features are creamy-brownish to grayish white fruiting bodies, spore-sac of small size, stem slender, gleba orange brown, spores are large, subglobose, regularly verrucose, up to 10.6 μm. Warts are large, 6–7 in number on the visible side of spore, up to 0.9 μm length, more or less isolated or merging into groups with small warts or forming ridge-like anastomoses at the base visible on SEM. It grows in scattered shrub communities with Caragana pygmaea, on dry sandy soil in south of Siberia. Based on the sequences of internal transcribed spacer (ITS1-5.8S-ITS2 = ITS) and D1/D2 domain of large subunit (28S) of nuc ribosomal DNA, we reconstructed a phylogeny of the genus Tulostoma. We present the detailed description of new species, color photos of fruiting bodies, light microscopy of anatomical characters, and analysis of morphological features in comparison with related species. To differentiate species of the genus Tulostoma necessary to use scanning electron microscopy. Therefore, we present photographs of spores of a new species under SEM. The DNA sequences obtained by us can also be used for identification of new species.